The double whammy of ER-retention and dominant-negative effects in numerous autosomal dominant diseases: significance in disease mechanisms and therapy - Nesrin Gariballa; Feda Mohamed; Sally Badawi; Bassam R. Ali (Journal of Biomedical Science, 2024)
Abstract The endoplasmic reticulum (ER) employs stringent quality control mechanisms to ensure the integrity of protein folding, allowing only properly folded, processed and assembled proteins to exit the ER and reach their functional destinations. Mutant proteins unable to attain their correct tertiary conformation or form complexes with their partners are retained in the ER and subsequently degraded through ER-associated protein degradation (ERAD) and associated mechanisms. ER retention contributes to a spectrum of monogenic diseases with diverse modes of inheritance and molecular mechanisms. In autosomal dominant diseases, when mutant proteins get retained in the ER, they can interact with their wild-type counterparts. This interaction may lead to the formation of mixed dimers or aberrant complexes, disrupting their normal trafficking and function in a dominant-negative manner. The combination of ER retention and dominant-negative effects has been frequently documented to cause a significant loss of functional proteins, thereby exacerbating disease severity. This review aims to examine existing literature and provide insights into the impact of dominant-negative effects exerted by mutant proteins retained in the ER in a range of autosomal dominant diseases including skeletal and connective tissue disorders, vascular disorders, neurological disorders, eye disorders and serpinopathies. Most crucially, we aim to emphasize the importance of this area of research, offering substantial potential for understanding the factors influencing phenotypic variability associated with genetic variants. Furthermore, we highlight current and prospective therapeutic approaches targeted at ameliorating the effects of mutations exhibiting dominant-negative effects. These approaches encompass experimental studies exploring treatments and their translation into clinical practice.